ANALISIS PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP TERJADINYA NON-PERFORMING LOAN (Studi Kasus pada Bank Umum Konvensional yang Menyediakan Layanan Kredit Pemilikan Rumah Periode 2008-2011) - Diyanti, Anin; Tri Widyarti, Endang (Faculty of Economics and Business Diponegoro University, 2012)
This research aim is to knowÂ about internal factors and external factors which are influences for the Non-Performing Loan (case studies on Conventional Commercial Banks in Indonesia that provide mortgage in period 2008 -2011). This research was conducted with purposive sampling. The samples used were 28 conventional commercial banks in Indonesia that provide mortgage in period 2008-2011. The data used in this study were obtained from the Banking Annual Report 2008-2011. Methods of data analysis using multiple linear regression analysis to determine the effect of Bank Size, Loan Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Gross Domestic Product (GDP) and Inflation to Non-Performing Loan (NPL) of Conventional Commercial Banks in Indonesia that provide mortgage in period 2008 -2011. Based on the test for normality, multicollinearity test, heteroskedastisitas test and autocorrelation test, there were no deviations from goodness of fit. This indicates that the available data has been qualified to use the model of multiple linear regression equation. From the analysis indicates that Bank Size, Capital Adequacy Ratio (CAR), Growth of Gross Domestic Product (GDP) and Inflation have a significant effect on Non-Performing Loan (NPL), whereas Loan Deposit Ratio (LDR) have no significance effect. Predictive capability of the five variables to Non-Performing Loan (NPL) of 30,4%, while the remaining 69,6% influenced by other factors not included in the research model.